Acquisition of cervical control through high postures in patients with West Syndrome: a case report. - Martins, Tamiris Beppler; Pires, Shaiane Alves; Castilho, Tayná; Rafael, Aline Dandara; Martinello, Micheli; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: early identification of neurological disorders is considered important in the assessment of risk factors and early treatment and subsequently in monitoring the child. Objective: report the lived experiences in a physiotherapy program based on high neuro‑evolutive postures in the development of the cervical and trunk control in a child diagnosed with West Syndrome, cerebral palsy and hydrocephalus. Methods: female child, chronological age of four years and five months, motor age less than three months. Kinetic and functional assessment was performed and the Gross Motor Function Measure (GMFM) and the Gross Motor Function Classification System (GMFCS) was used to characterize the subject. Results: there was an increase to 68.6% in the GMFM, maintaining the level of the GMFCS, improvement of cervical and trunk control in sitting and standing position and when were performed postural changes. Conclusion: the physiotherapeutic care proved to be beneficial in the gradual development of cervical and trunk motor control.